Improved Hydrothermal Conversion of Pea Pod Biomass for Production of Platform Chemicals with Organic Acid Catalysts - Alejandra Sophia Lozano Pérez; Valentina Romero Mahecha; Luis Enrique Cuca Suarez; Carlos Alberto Guerrero Fajardo (ChemEngineering)
Agro-industries produce over 2 billion tons of agricultural waste annually, including by-products like bagasse, molasses, seeds, stems, leaves, straw, and shells. The use of agro-industrial waste is a way to reduce the impact of industrial processes on the environment. The pea pod is a biomass with a high concentration of cellulose, hemicellulose and some lignin; therefore, it can be used to produce platform chemicals by means of a hydrothermal process. There is limited research on the hydrolysis of pea biomass, but it has been shown to obtain high yields. This study analyzed the effectiveness and selectivity of the hydrothermal process using pea pod biomass with a particle size of 0.5 mm at 180 °C for one hour. A 500 mL reactor was used, with a biomass-to-acid solution ratio of 1:20. The concentration of the acid solution was 0.02 M. The concentrations of sugar, formic acid, levulinic acid, HMF, and furfural produced were measured. Among the catalysts studied, adipic acid catalysis showed the highest yield of 65.16%, with 37.09% of sugar, 16.37% of formic acid, and 11.71% of levulinic acid. On the other hand, the catalysts with chloroacetic acid, butyric acid, anthranilic acid, and phthalic acid were less effective but demonstrated selectivity for sugar production, proving that the liquid phase obtained using the catalyst with those acids can be used as carbon sources for a fermentation process. In general, when comparing the process with or without the use of a catalyst, it is observed that with a catalyst in the reaction, the amount of HMF and furfural produced is reduced and the selectivity with respect to sugar production is increased.